Granzyme A potentiates chemokine production in IL‐17‐stimulated keratinocytes. Issue 9 (10th April 2017) - Cheuk, Stanley; Martini, Elisa; Bergh, Kerstin; Chang, David; Rethi, Bence; Ståhle, Mona; Eidsmo, Liv
Abstract: Plaque psoriasis presents with focal skin inflammation, partially maintained by IL‐17‐mediated interactions between infiltrating epidermal T cells and activated keratinocytes. Here we show that the majority of lesional epidermal CD8 T cells express granzyme A, alone or in combination with IL‐17. To assess proinflammatory properties of granzyme A in psoriasis, primary human keratinocytes were stimulated with granzyme A in the presence or absence of IL‐17. Out of 33 analysed keratinocyte‐derived inflammatory mediators, granzyme A potentiated IL‐17‐induced secretion of CXCL 1, CXCL 12 and CCL 4. Intriguingly, all three chemokines are implicated in psoriasis pathogenesis and are involved in recruitment of T cells, neutrophils and pDCs into inflamed tissues. Our results indicate that granzyme A produced by lesional CD8 T cells specifically increase the chemokine production from inflamed keratinocytes, thereby amplifying a chemotactic inflammatory loop that sustains psoriasis lesions.